Effect of food on the pharmacokinetics of canagliflozin, a sodium glucose co‐transporter 2 inhibitor, and assessment of dose proportionality in healthy participants. Issue 4 (11th December 2014) - Devineni, Damayanthi; Manitpisitkul, Prasarn; Murphy, Joseph; Stieltjes, Hans; Ariyawansa, Jay; Di Prospero, Nicholas A.; Rothenberg, Paul
Abstract Canagliflozin, an orally active inhibitor of sodium glucose co‐transporter 2, is approved for the treatment of type‐2 diabetes mellitus. The effect of food on the pharmacokinetics of 300 mg canagliflozin, and dose proportionality of 50, 100, and 300 mg canagliflozin, were evaluated, in two studies, in healthy participants. Study 1 used a randomized, 2‐way crossover design: canagliflozin 300 mg/day was administered under fasted (Period‐1) and fed (Period‐2) conditions or vice versa. Study 2 was a 3‐way crossover: participants were randomized to receive three single‐doses of canagliflozin (50, 100, and 300 mg), one in each period. In both studies, treatment periods were separated by washout intervals of 10–14 days, and pharmacokinetics assessed up to 72 hours postdose of each treatment period. No clinically relevant food effects on canagliflozin exposure parameters were observed: 90% confidence intervals (CIs) for the fed/fasted geometric mean ratios of AUC∞ (ratio: 100.51; 90% CI: 89.47–112.93) and Cmax (ratio: 108.09; 90% CI: 103.45–112.95) were entirely within bioequivalence limits (80–125%). Plasma canagliflozin exposures were dose‐proportional as the 90% CI of the slope of the regression line for dose‐normalized AUC∞ and Cmax fell entirely within the prespecified limits of −0.124 to 0.124. No clinically significant safety issues were noted, and canagliflozin was generally well‐tolerated.